The association between diffusion of the surgical robot and radical prostatectomy rates - Makarov, Danil V; Yu, James B; Desai, Rani A; Penson, David F; Gross, Cary P (Medical care, 2011)
Despite its expense and controversy surrounding its benefit, the surgical robot has been widely adopted for the treatment of prostate cancer. To determine the relationship between surgical robot acquisition and changes in volume of radical prostatectomy (RP) at the regional and hospital levels. Retrospective cohort study. Men undergoing RP for prostate cancer at nonfederal, community hospitals located in the states of Arizona, Florida, Maryland, North Carolina, New York, New Jersey, and Washington. Change in number of RPs at the regional and hospital levels before (2001) and after (2005) dissemination of the surgical robot. Combining data from the Healthcare Cost and Utilization Project State Inpatient Databases 2001 and 2005 with the 2005 American Hospital Association Survey and publicly available data on robot acquisition, we identified 554 hospitals in 71 hospital referral regions (HRR). The total RPs decreased from 14,801 to 14,420 during the study period. Thirty six (51%) HRRs had at least 1 hospital with a surgical robot by 2005; 67 (12%) hospitals acquired at least 1 surgical robot. Adjusted, clustered generalized estimating equations analysis demonstrated that HRRs with greater numbers of hospitals acquiring robots had higher increases in RPs than HRRs acquiring none (mean changes in RPs for HRRs with 9, 4, 3, 2, 1, and 0 are 414.9, 189.6, 106.6, 14.7, -11.3, and -41.2; P<0.0001). Hospitals acquiring surgical robots increased RPs by a mean of 29.1 per year, while those without robots experienced a mean change of -4.8, P<0.0001. Surgical robot acquisition is associated with increased numbers of RPs at the regional and hospital levels. Policy makers must recognize the intimate association between technology diffusion and procedure utilization when approving costly new medical devices with unproven benefit.